Modul pembelajaran baik pulih komputer secara maya - A'alaf, Rasyida (2003)
In this Infonnation and Communication Technology era, educational system has undergone a lot of changes. Many electronic virtual learning systems were developed for students and educational institutions. Such systems offer many advantages not only for students but also for, users either direct or indirect. Based on this, an electronic learning module for Computer Maintenance is developed. A study was conducted on sixty-five, 4th semester polytechnic students. They are undergoing Certificate in Electrical Engineering (Computer Technology). Questionnaire is used, and the result is analyzed through Statistical Package For Social Science 11.0 for Windows (SPSS) software. The findings show that the respondents are happy to use this module. Learning is made easier for them.